2018
DOI: 10.1016/j.jstrokecerebrovasdis.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Human Immunodeficiency Virus-infected Individuals in Sub-Saharan Africa (SSA): A Systematic Review

Abstract: Stroke in PLWH in SSA occurs at a young age, in those with advanced disease, and is associated with worse outcomes than in HIV-uninfected comparators. Stroke in young individuals in the region should prompt HIV testing, and ongoing efforts to promote early antiretroviral therapy initiation might also help decrease stroke incidence, morbidity, and mortality in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 43 publications
3
41
4
1
Order By: Relevance
“…3 Previous studies estimate an incidence of approximately 1% to 6.4% of stroke in children with HIV, although studies following autopsy have shown much higher rates of up to 34%. 16,36,37 In both Malawian and Zambian populations, HIV infection has been associated with stroke in young adults, but most studies of HIV and stroke have not included subjects younger than 18 years. 38,39 HIV is known to cause cerebral vasculopathy, 40 angiitis, 41 aneurysmal dilatation 42 (particularly fusiform aneurysms in children 43 ), arterial stenosis complicated by ischemic infarction, 44 and secondary moyamoya syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Previous studies estimate an incidence of approximately 1% to 6.4% of stroke in children with HIV, although studies following autopsy have shown much higher rates of up to 34%. 16,36,37 In both Malawian and Zambian populations, HIV infection has been associated with stroke in young adults, but most studies of HIV and stroke have not included subjects younger than 18 years. 38,39 HIV is known to cause cerebral vasculopathy, 40 angiitis, 41 aneurysmal dilatation 42 (particularly fusiform aneurysms in children 43 ), arterial stenosis complicated by ischemic infarction, 44 and secondary moyamoya syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…45 Although there is significant literature on HIV-associated cerebrovascular disease, its precise mechanism is not known. 24,36,46 Adult studies have found that stroke is not common in HIV without an additional underlying disease state. 47 These disease states include infections including varicella zoster virus, 42 cryptococcus, 48,49 neurocysticercosis, 50 hepatitis B, 51 syphilis, 52 and tuberculosis, 53 as well as neoplastic and prothrombotic states.…”
Section: Discussionmentioning
confidence: 99%
“…In this specific region, stroke was commonly found to be the first manifestation of HIV infections. In a systematic review, over 90% of young adults with stroke in sub-Saharan Africa with HIV were ischaemic strokes and stroke patients with HIV often had a coagulopathy and more severe stroke compared with young adults with stroke without HIV 27. Similarly, these findings may also be found in other developing countries.…”
Section: Epidemiology and Stroke Aetiology From A Global Perspectivementioning
confidence: 91%
“…Other infections are also associated with a high risk of ischaemic stroke, including HIV, neurocysticercosis and tuberculosis. HIV has a high prevalence in sub-Saharan Africa with over two-thirds of the world’s population 27 28. In this specific region, stroke was commonly found to be the first manifestation of HIV infections.…”
Section: Epidemiology and Stroke Aetiology From A Global Perspectivementioning
confidence: 99%
“…There have been numerous mechanisms proposed to explain this. A systematic review done by Addallah et al 37 reported that this could be due to HIV-associated opportunistic infections, HIV-induced coagulopathy, and chronic inflammatory processes that can accelerate atherosclerosis. Another systematic review by Bogorodskaya et al 38 also reported that some antiretrovirals (lopinavir, indinavir, and abacavir) were also associated with an increased risk of stroke.…”
Section: Discussionmentioning
confidence: 99%